Perception of threat and efficacy in contracting COVID-19 infection among tobacco users – A cross-sectional analytical study from four Indian States - Sitanshu Sekhar Kar; Neema Joseph; Sonu Goel; Rana J Singh; Binod Kumar Patro; Star Pala; Rajeev Kumar; Bishwaranjan Purohit; Shravan Kumar Medini; Ory Nica Kharbangar; Jeyanthi Anandraj (Indian Journal of Public Health, 2023)
Background: To trigger quit intention and practice of preventive measures for COVID-19 among tobacco users; it is imperative for them to be well aware of the fact that they are at higher risk of COVID-19 infection and should be at higher efficacy to practice preventive measures for the disease as compared to nonusers of tobacco. Objectives: This community-based cross-sectional analytical study was conducted from April 2020 to May 2020 among 1203 adult participants to compare the threat and efficacy perception among users and nonusers of tobacco. Materials and Methods: Perception of threat was assessed using three questions on perceived threat and one question on perceived susceptibility; whereas perception of efficacy was assessed using four questions each on self-efficacy and response efficacy through telephonic interview. Results: There was no significant difference in the overall threat perception among users and nonusers of tobacco. However, state-wise analysis showed that tobacco users had higher perception of threat for SARS-CoV-2 infection in all the states except Telangana. The overall perception of efficacy among tobacco users was significantly higher as compared to nonusers of tobacco. Conclusion: The study calls for active collaboration between tobacco control enthusiasts and the Government to promote awareness of a higher risk of COVID-19 disease among tobacco users. In essence, the study's implications extend beyond COVID-19 and can guide targeted efforts to promote awareness, behavior change, and collaboration in the context of other infectious diseases among tobacco users.